Predictors of Fall Protective Behaviors Among Iranian Community-Dwelling Older Adults: An Application of the Protection Motivation Theory - Taheri-Kharameh Z (Dove Medical Press, 2020)
Zahra Taheri-Kharameh,1 Saeed Bashirian,2 Rashid Heidarimoghadam,3 Jalal Poorolajal,4 Majid Barati,2 Éva Rásky5 1Student Research Committee, Department of Public Health, Hamadan University of Medical Sciences, Hamadan, Iran; 2Department of Public Health, School of Health, Social Determinants of Health Research Center, Hamadan University of Medical Sciences, Hamadan, Iran; 3Department of Ergonomics, School of Health, Research Center for Health Sciences, Hamadan University of Medical Sciences, Hamadan, Iran; 4Research Center for Health Sciences, Department of Epidemiology, School of Public Health, Hamadan University of Medical Sciences, Hamadan, Iran; 5Institute of Social Medicine and Epidemiology, Medical University of Graz, Graz, AustriaCorrespondence: Majid BaratiDepartment of Public Health, Hamadan University of Medical Sciences, Hamadan, IranTel +988138380090Email Barati@umsha.ac.irPurpose: The protection motivation theory (PMT) is a common framework understanding the use of protective behaviors. The aim of this study was to assess the predictors of fall protective behaviors among community-dwelling older adults, Iran.Methods: The cross-sectional study was conducted in Qom, Iran, from May to October 2018. Three hundred older people were selected from retirement centers via stratified sampling method. Data were collected by a questionnaire containing items on socio-demographic information, Falls Behavioral (FaB) Scale, and PMT constructs scale. Data analysis was performed using descriptive statistics and structural equation modeling.Results: The mean (SD) age of the participants was 64.6 (5.5) and the majority were male (77.7%). Level of perceived fall threat was lower than perceived efficacy of fall protective behaviors. There was a significant relationship between protection motivation and fall protective behaviors (β= 0.515, t-value= 13.650). Coping appraisals (β= 0.409, t-value= 7.352) and fear (β= 0.194, t-value= 2.462) were associated with motivation. The model explained approximately 27% of the variance in fall protective behaviors. The goodness of fit index of 0.48 indicating the model good fit.Conclusion: The results indicated that protection motivation, coping appraisals and reasonable fear are considered as the strongest predictors of fall protective behaviors among older people. The results can help health care providers to develop appropriate interventions to fall prevention among older people.Keywords: fall prevention, protection motivation theory, coping appraisals, threat appraisals, aging